2020
DOI: 10.1002/nop2.470
|View full text |Cite
|
Sign up to set email alerts
|

Nursing diagnosis identification by nurses in burn wards: A descriptive cross‐sectional study

Abstract: Aim To identify and document patients' care needs, it is vital to provide quality care services. This study was aimed to describe care needs derived from records of patients with burn and to evaluate whether nurses employed the North American Nursing Diagnosis Association classification to formulate patients' care needs. Design A descriptive cross‐sectional study. Methods In this study using the convenient sampling method, 430 nursing records reviewed in the burn wards. Data were collected using Gordon's check… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 25 publications
1
7
0
1
Order By: Relevance
“…These studies have reported that the quality of nursing documentation was unsuitable and did not contain necessary information (Rajabpoor et al, 2018;Moghadas & Sedaghati Kesbakhi, 2020;Ghafouri Fard et al, 2012;Tab rizi et al, 2016;Zamanzadeh et al, 2015). Results of this study showed that the top prevalent nursing diagnoses were the risk for infection, which is consistent with the results of Khajehgoodari's study and case study by Vinicius Lino Souza Neto and colleagues (Khajehgoodari et al;Neto et al, 2018)…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…These studies have reported that the quality of nursing documentation was unsuitable and did not contain necessary information (Rajabpoor et al, 2018;Moghadas & Sedaghati Kesbakhi, 2020;Ghafouri Fard et al, 2012;Tab rizi et al, 2016;Zamanzadeh et al, 2015). Results of this study showed that the top prevalent nursing diagnoses were the risk for infection, which is consistent with the results of Khajehgoodari's study and case study by Vinicius Lino Souza Neto and colleagues (Khajehgoodari et al;Neto et al, 2018)…”
Section: Discussionsupporting
confidence: 79%
“…A study in Brazil showed that a smaller number of recordings were done in the steps relative to nursing diagnosis and evolution (Reppetto & Souza, 2005 ). A study in the same hospital showed that nurses' awareness of nursing diagnoses was very poor (Khajehgoodari et al., 2020 ). Studies on nursing documentation in Iran have focused more on the quality of nursing documentation.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, most nurses do not have enough autonomy to use a nebulizer for patients based solely on their clinical judgment and instead require a specific physician order to do so. Given that nurses provide nursing care according to the orders of physicians and the patient care needs are not planned by nurses, it can be concluded that in this specific context, the documentation of activities reflects physician‐driven interventions rather than a culmination of nurses’ critical thinking and care planning (Khajehgoodari et al., 2020). As it has been recently demonstrated, the quality of nursing diagnoses in Iran is not high enough to provide a nursing care plan (Lotfi et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Nursing assessment is vital to quality nursing care. However, there is not enough value placed on the role of the assessment in nursing practice, which can be depicted from the lack of its implementation and incomplete patient documentation (Diniz et al 2015;Khajehgoodari et al, 2020). Barriers to conduct nursing assessment have been identified and include lack of nursing role models, and influence on nursing care and on patient outcomes (Douglas et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Barriers to conduct nursing assessment have been identified and include lack of nursing role models, and influence on nursing care and on patient outcomes (Douglas et al, 2014). The lack of a nursing framework to guide nursing assessment may lead to inaccurate diagnoses of patients' needs from a nursing perspective and invisibility of the nursing profession (Khajehgoodari et al, 2020). Gordon's Eleven FHP (Gordon, 1994) can contribute positively to assist nurses during the continuum of nursing care (Temel & Kutlu, 2015;Türen & Enç, 2020).…”
Section: Discussionmentioning
confidence: 99%